An exploration of actions to forge public entrepreneurship in the implementation of the expanded public works programme in the Eastern Cape - Mageza, Quinton Qengeba (Graduate School of Development Policy and Practice, 2016)
The dissertation begins by outlining the history and objectives of the Expanded Public Works Programme (EPWP) as one of the key government interventions to address poverty and unemployment. The paper moves on to analyse the Vukuzakhe programme which is an initiative of the Eastern Cape Department of Roads and Public Works within the infrastructure sector of the EPWP. This analysis looks at policy assumptions in respect of institutional arrangements that informed the development and implementation of the Vukuzakhe Programme. The study goes on to identify and assess the outcomes of public entrepreneurship with the context of the Vukuzakhe programme. The hypotheses made are that: A: "The success of the Vukuzakhe programme was as the result of effective acts of public entrepreneurship." B: "The successful and effective acts of public entrepreneurship were demonstrated in the way in which change was orchestrated and directed, through the building of internal capacity and ability to marshal support from diverse stakeholders."